Increase of integrin α6+p63+ cells after ultraviolet B irradiation in normal human keratinocytes - Gyeong-hun Park; Seung-seog Han; Sung-eun Chang; Jee-ho Choi (PAGEPress Publications, 2009)
Epidermal stem cells (SC) are believed to be resistant to environmental damage for the purpose of self renewal. Most promising SC markers include integrin a6 and p63. The aim of our study was to determine whether the integrin a6+p63+ cell fraction representative of the epidermal progenitor or SC is increased after ultraviolet B (UVB) irradiation and to clarify the hypothesis that epidermal SC are resistant to high-dose UVB damage. We irradiated early passage normal human keratinocytes (NHK) with 0, 25, 50, and 100 mJ/cm2 UVB. The percentage of cell death was calculated. Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) and western blotting analyses were performed to identify integrin a6 and p63, and flow cytometry analysis with integrin a6 and p63 antibodies was done. After 50 and 100 mJ/cm2 UVB, integrin a6+p63+cells were found to be much increased by fluorescence-activated cell sorting. Expression of integrin a6 and p63 was increased in NHK after UVB irradiation, which was shown with real-time RT-PCR and western blotting analyses. We concluded that an increase of integrin a6+p63+ cells after high-dose UVB may suggest that the putative progenitor or SC are resistant to UVB irradiation.